2021
DOI: 10.1111/bcp.14841
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐PCSK 9 antibodies increase the ratios of the brain‐specific oxysterol 24S‐hydroxycholesterol to cholesterol and to 27‐hydroxycholesterol in the serum

Abstract: Aims:The serum ratios of the brain-specific oxysterol 24S-hydroxycholesterol (24S-OHC) to cholesterol and to 27-OHC reflect brain cholesterol turnover. We studied the effect of proprotein convertase subtilisin/kexin type 9 monoclonal antibodies (PCSK9ab) that enhance low-density lipoprotein receptor activity on serum cholesterol and oxysterol concentrations.Methods: Twenty-eight hypercholesterolaemic patients (15 males and 13 females) responding insufficiently to maximally tolerated statin and/or ezetimibe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…113 One study demonstrated increased excretion of 24S-hydroxycholesterol from the brain in response to PCSK9 inhibitor therapy. 114 Whether inclisiran, an siRNA that inhibits the translation of the PCSK9 mRNA, crosses the BBB is not known. 115 PCSK9 inhibitors, through an increase in LDL receptors, could theoretically increase brain absorption of cholesterol from the periphery.…”
Section: Brain Metabolism Of Cholesterol and Potential Effect Of Chol...mentioning
confidence: 99%
“…113 One study demonstrated increased excretion of 24S-hydroxycholesterol from the brain in response to PCSK9 inhibitor therapy. 114 Whether inclisiran, an siRNA that inhibits the translation of the PCSK9 mRNA, crosses the BBB is not known. 115 PCSK9 inhibitors, through an increase in LDL receptors, could theoretically increase brain absorption of cholesterol from the periphery.…”
Section: Brain Metabolism Of Cholesterol and Potential Effect Of Chol...mentioning
confidence: 99%
“…The effects of evolocumab and alirocumab on lipidome profile were evaluated in hypercholesterolemic patients responding insufficiently to maximally tolerated statin and/or ezetimibe therapy. The brain-specific oxysterols 24S-OHC and 27-OHC were assessed by isotope dilution GC-MS selected ion-monitoring (GC–MS-SIM) by using the corresponding deuterium-labelled oxysterols as internal standards, before, after 1-month and after 3-month of treatment ( 91 ). 24S-OHC ratios to cholesterol and to 27-OHC in serum or plasma are thought to be potential biomarkers for brain cholesterol metabolism ( 92 ).…”
Section: Agnostic Evaluation Of Pcsk9 Effects By Proteomics and Lipid...mentioning
confidence: 99%
“…24S-OHC ratios to cholesterol and to 27-OHC in serum or plasma are thought to be potential biomarkers for brain cholesterol metabolism ( 92 ). After 1-month of treatment, evolocumab and alirocumab significantly reduced serum total cholesterol, LDL-C and 27-OHC concentrations, whereas serum ratios of 24S-OHC to cholesterol and 24S-OHC to 27-OHC increased, reaching even higher levels within 3 months of treatment ( 91 ). The authors suggested that this specific brain cholesterol turnover was probably due to lower levels of 27-OHC in the brain, resulting in increased synthesis of brain cholesterol, higher production of 24S-OHC and its secretion across the blood-brain barrier.…”
Section: Agnostic Evaluation Of Pcsk9 Effects By Proteomics and Lipid...mentioning
confidence: 99%